EFFECTIVENESS OF CINNAMON TEA IN REDUCING WEIGHT AMONG LATE OBESE ADOLESCENCE - GOWRI P, MANGALA; T, MARY MINOLIN; P, Thenmozhi; P, Meena; S, Vimala (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the study is to determine the effectiveness of cinnamon tea in reducing weight among late obese adolescent. Methods: Pre experimental research design was adopted to conduct the study with 30 samples who met the inclusion criteria. Cinnamon tea was given for the samples for 15 days andÂ  theirweight and BMI was measured before as well as after the intervention. Data were analyzed by using descriptive and inferential statistics. Results:Out of 30 samples in pretest, 70% of them had overweight and 30% of them had class I obesity with the BMI mean value of 28.75 and2.72 standard deviation. In posttest 20% of them were normal weight, 66.67% of them were overweight and 13.33% of them were Class I obesity.The posttest BMI mean was 27.45 with 3.34 standard deviation. Paired t test revealed that Cinnamon tea was found to be effective in reducing weight at the level of *P<0.05. Conclusion:the findings of the present study revealed that the prescribed cinnamon tea resulted in an improvement reduction of weight. However, we need further studies with larger samples to investigate the effect of cinnamon in reducing the different factors like weight, BMI, hip waist circumference level in obese adolescents. Keywords: Obesity, Childhood obesity, Adolescent, Cinnamon, BMI, Weight, Cinnamon tea Â 